Mortality in psychotic depression: 18-year follow-up study - Tapio Paljärvi; Jari Tiihonen; Markku Lähteenvuo; Antti Tanskanen; Seena Fazel; Heidi Taipale (2022)
Background Evidence on the role of co-occurring psychiatric disorders in mortality associated with psychotic depression is limited. Aims To estimate the risk of cause-specific mortality in psychotic depression compared with severe non-psychotic depression while controlling for comorbid psychiatric disorders. Method This cohort study used routine data from nationwide health registers in Finland. Eligible participants had their first diagnosis for psychotic depression or for severe non-psychotic depression between the years 2000 and 2018, had no pre-existing diagnoses for schizophrenia spectrum disorders or bipolar disorder, and were aged 18–65 years at the index diagnosis. Causes of death were defined by ICD-10 codes. The follow-up time was up to 18 years. Results We included 19 064 individuals with incident psychotic depression and 90 877 individuals with incident non-psychotic depression. Half (1199/2188) of the deaths in those with psychotic depression occurred within 5 years from the index diagnosis and the highest relative risk was during the first year after the diagnosis. Compared with individuals with non-psychotic depression, those with psychotic depression had a higher risk of all-cause mortality (adjusted hazard ratio, aHR = 1.59, 95% CI 1.48–1.70), suicides (aHR = 2.36, 95% CI 2.11–2.64) and fatal accidents (aHR 1.63, 95% CI 1.26–2.10) during the subsequent 5-year period after the index diagnosis. Conclusions Psychotic symptoms markedly added to the mortality risk associated with severe depression after controlling for psychiatric comorbidity. Prompt treatment and enhanced monitoring for psychotic symptoms is warranted in all patients with severe depression to prevent deaths because of suicides and other external causes.